2015
DOI: 10.1073/pnas.1424706112
|View full text |Cite
|
Sign up to set email alerts
|

Lack of exercise leads to significant and reversible loss of scale invariance in both aged and young mice

Abstract: In healthy humans and other animals, behavioral activity exhibits scale invariance over multiple timescales from minutes to 24 h, whereas in aging or diseased conditions, scale invariance is usually reduced significantly. Accordingly, scale invariance can be a potential marker for health. Given compelling indications that exercise is beneficial for mental and physical health, we tested to what extent a lack of exercise affects scale invariance in young and aged animals. We studied six or more mice in each of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 36 publications
2
33
0
Order By: Relevance
“…Rodent studies have also shown that access to running wheels can substantially affect the distribution, amount, and architecture of vigilance states and activity across 24 hours, 151 , 152 as well as EEG SWA. 98 Notably, frontal predominance of SWA was enhanced after a period of waking without running wheel activity leading the authors to hypothesize that more diverse waking behaviors and activity led to a higher need for local or global “recovery”.…”
Section: Sleep and Recovery After Physical Fatiguementioning
confidence: 99%
“…Rodent studies have also shown that access to running wheels can substantially affect the distribution, amount, and architecture of vigilance states and activity across 24 hours, 151 , 152 as well as EEG SWA. 98 Notably, frontal predominance of SWA was enhanced after a period of waking without running wheel activity leading the authors to hypothesize that more diverse waking behaviors and activity led to a higher need for local or global “recovery”.…”
Section: Sleep and Recovery After Physical Fatiguementioning
confidence: 99%
“…In this study, we performed continuous recordings of neuronal activity from two cortical regions in mice given free access to running wheels (RWs). Previously, it has been shown that spontaneous wheel running is associated with distinct changes in the architecture and distribution of vigilance states across 24 h, and leads to regional changes in waking and sleep EEG 27 28 29 30 . On the other hand, several studies performed in head-fixed animals showed that locomotion affects neuronal activity in a cortical region, and cell type-specific manner 6 7 8 9 13 .…”
mentioning
confidence: 99%
“…2). Indeed, locomotor activity has also been reported to improve rhythms both in aged mice [38] and in mutant strains with disrupted SCN intercellular synchrony [8], whilst a lack of exercise has been reported to reduce scale invariance of behavioural rhythms, a marker of general health [55]. Further, the timing of exercise within a lightdark cycle has been shown to be important for the degree of protection offered by exercise against weight gain on a high fat diet [56], and simulated shift-work desynchronises liver gene expression, disrupting metabolism [47].…”
Section: Discussionmentioning
confidence: 99%